ETOS KERJA MASYARAKAT NELAYAN KECIL KELURAHAN BAGAN DELI, BELAWAN, MEDAN - Eko Prasetyo Ritanto (Sabda: Jurnal Kajian Kebudayaan, 2018)
The fishing community is a social element that is very important in the structure of coastal communities which they had colored cultural characteristics and socio-cultural behavior of coastal communities in particular that of Bagan Deli, Belawan, Medan. This study views their work ethic differences between the shipmen/crew, skipper/captain and ship owner that caused the differences of their social stratification. Using a qualitative method and non-parametric statistical analysis of kolmogorov smirnov, this study results that the work ethic among the crew and skipper there has no differences, whereas between the crew and the skipper with the owners there are differences in higher ethic.